2019
DOI: 10.3389/fbioe.2019.00250
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Analysis of Long Repeats of Proteins at the Domain Level

Abstract: Amino acid repeats play an important role in the structure and function of proteins. Analysis of long repeats in protein sequences enables one to understand their abundance, structure and function in the protein universe. In the present study, amino acid repeats of length >50 (long repeats) were identified in a non-redundant set of UniProt sequences using the RADAR program. The underlying structures and functions of these long repeats were carried out using the Gene3D for structural domains, Pfam for functiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Protein sequence analysis by using the RADAR (Rapid Automatic Detection and Alignment of Repeats in protein sequences tool, https://www.ebi.ac.uk/Tools/pfa/radar/ ) showed that both proteins harbor several highly homologous domains [21] . A previous study suggests that such organization of three/four long repeat sequences may hint to an important role in the structure and function of the protein [22] . TMHMM (TransMembrane prediction using Hidden Markov Models, https://dtu.biolib.com/DeepTMHMM ) [23] analysis predicted that both proteins have a secretion signal and a transmembrane sequence at their N-terminus [24] .…”
Section: Resultsmentioning
confidence: 95%
“…Protein sequence analysis by using the RADAR (Rapid Automatic Detection and Alignment of Repeats in protein sequences tool, https://www.ebi.ac.uk/Tools/pfa/radar/ ) showed that both proteins harbor several highly homologous domains [21] . A previous study suggests that such organization of three/four long repeat sequences may hint to an important role in the structure and function of the protein [22] . TMHMM (TransMembrane prediction using Hidden Markov Models, https://dtu.biolib.com/DeepTMHMM ) [23] analysis predicted that both proteins have a secretion signal and a transmembrane sequence at their N-terminus [24] .…”
Section: Resultsmentioning
confidence: 95%
“…Thus, proteins with repeats represent structural elements of cells and tissues (e.g., collagen and keratin) and provide a framework for protein-protein interactions [8] or, conversely, prevent cross-domain aggregation [9]. They may have catalytic [10] or inhibitory activity [11]. Furthermore, changes in the number of repetitive motifs and their consensuses can lead to genetic diseases [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Several web servers and tools such as RADAR, TRUST, XSTREAM, T-REKS, and PTRStalker etc., that use different methods of sub-optimal alignment, short seed expansion, K-means clustering and normalized BLOSUM-weighted edit distance [9][10][11][12][13] for repeats detection have been developed. Further, the repeats in the sequences of Protein Data Bank (PDB) [14] and UniProtKB/Swiss-Prot [15] identified by using RADAR have been analyzed at the structural and functional level. Several databases for amino acid repeats from different set of protein sequences were constructed for large scale analysis.…”
Section: Introductionmentioning
confidence: 99%